Planejamento e projeto do produto para demanda de tecnologia assistiva: metodologia de solução inventiva para o desenvolvimento de órtese - Paulo Henrique Rodrigues Guilherme Reis (2022)
The use of orthoses, static and dynamic, is an efficient way to treat hand impairments and limitations, often caused by brain injuries, such as Cerebral Palsy and motor dysfunctions. However, although highly recommended by professionals in the area, the use of orthoses is often neglected due to the high cost of acquisition, discomfort of the device, and complexity of use and maintenance. In this context, this study aims to present the process and development of two hand orthoses, being a static one, for positioning, and a dynamic one, for increasing functionality. The static orthosis model was developed from Topology Optimization. To validate the new model, numerical simulations were performed by Finite Element Analysis and Thermographic Studies were compared to the traditional model. The results show that the new model, when compared to the traditional model, presents a 17.56% reduction in the volume of material used, a 35.48% reduction in the weight of the orthosis, and a 171.17% reduction in the maximum surface deformation when subjected to the acting forces. It was also verified that, when manufactured by MA, the new model is 2.54 times cheaper than the traditional model besides presenting better cooling performance during use (max: 36.4ºC) if compared to the traditional model (max: 39.7ºC). The proposal of the dynamic orthosis was to develop a functional device with simplified activation. A torsion spring energy conserving mechanism was developed to enable hand functionality in individuals with Hemiplegic Cerebral Palsy. Clinical results of the dynamic orthosis demonstrated functionality of the device in both the activation of the pincer movement and the gripping force provided by the spring. Statistical analysis demonstrated superiority of functionality in the dynamic orthosis intervention compared to the intervention without the orthosis (p < 1000), however, no significant difference was indicated in the comparison of functionality between the interventions with the dynamic orthosis and without the orthosis.